4ax-3b=b+20

Simple and best practice solution for 4ax-3b=b+20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4ax-3b=b+20 equation:


Simplifying
4ax + -3b = b + 20

Reorder the terms:
4ax + -3b = 20 + b

Solving
4ax + -3b = 20 + b

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3b' to each side of the equation.
4ax + -3b + 3b = 20 + b + 3b

Combine like terms: -3b + 3b = 0
4ax + 0 = 20 + b + 3b
4ax = 20 + b + 3b

Combine like terms: b + 3b = 4b
4ax = 20 + 4b

Divide each side by '4x'.
a = 5x-1 + bx-1

Simplifying
a = 5x-1 + bx-1

Reorder the terms:
a = bx-1 + 5x-1

See similar equations:

| -8d=80 | | 2-u=78 | | 7-9[7-(7y-4)]=0 | | x^4-2x^3+6x^2+8x-27=0 | | 11-18=63 | | -59+-2x=21-7x | | 4+3n=61 | | -[7z-(12z+4)]=4+(4z+1) | | (7p+2)3+8p= | | 8p^2+37p-15=0 | | 6+2=72 | | -10+5(c-3)=20 | | 2-(4x-7)=9-4x | | 3.5h+10=5.25h-10.25 | | 10x^2=2x+1 | | 9n^2-33n+28=0 | | -9(8+m)-13=-25 | | 9+8=15 | | 9-2=56 | | 7(x-4)+2=-19 | | -4.6+1.6=0.6 | | 12t-18=4(4t+2) | | 5-3=22 | | 2[k-(2k+8)+6]=2(k+2) | | 5n=2+2+2+2+2 | | 7-9=48 | | 4-8=60 | | 4x+12y=780 | | 350-280=70 | | 2(4x+5)-3=0 | | 6X-X^2-9=0 | | 2+7=45 |

Equations solver categories